2017
DOI: 10.5455/apd.237985
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and validity of Turkish Form of Severity of Acute Stress Symptoms Scale

Abstract: ÖZ

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 3 publications
0
2
0
1
Order By: Relevance
“…As is seen, death anxiety increased acutely after GI intervention. Therefore, the fact that GI, which psychologically put the nurses in the shoes of the terminally ill as though they themselves were the one dying can be asserted to increase death anxiety as acute stress response and then lower this anxiety [38]. In addition, in the present study, the nurses had high level of empathy when their death anxiety was high and this suggested that even though they had a real confrontation with death and got out of defence mechanisms leading them to display avoidant-negative attitudes, they could develop empathy with patients albeit their own anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…As is seen, death anxiety increased acutely after GI intervention. Therefore, the fact that GI, which psychologically put the nurses in the shoes of the terminally ill as though they themselves were the one dying can be asserted to increase death anxiety as acute stress response and then lower this anxiety [38]. In addition, in the present study, the nurses had high level of empathy when their death anxiety was high and this suggested that even though they had a real confrontation with death and got out of defence mechanisms leading them to display avoidant-negative attitudes, they could develop empathy with patients albeit their own anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…etkileri seyreder nitelikle olmalı ayrıca, travmatik deneyimden hemen sonra başlasa bile en az 3gün, en fazla bir ay sürmesi tanılamanın niteliklerini karşılaması bakımından gerekmektedir (Battal & Özmenler, 1997). Akut stres bozukluğu, kişinin toplumsal ve bireysel işlevsel kimliğinin düşmesine sebebiyet verebilmekte olup, en önemli ayırıcı etkenin depresif tetiklenmeler ile dissosiyatif özelliklerin meydana gelebilmesi şeklinde ifade edilmektedir (Aşçıbaşı et al, 2017).…”
Section: Akut Stres Bozukluğu Nedir?unclassified
“…The scale can help clinicians identify individuals who may need further assessment or treatment for acute stress disorder. For NSESSS, Ascibasi et al found adequate internal consistency in the Turkish population, with a Cronbach's alpha score of 0.95 18 .…”
Section: National Stressful Events Survey Acute Stress Disorder Short...mentioning
confidence: 99%